PERANCANGAN SISTEM PENUNJANG KEPUTUSAN INTELIJEN UNTUK SELEKSI KONSEP PRODUK BARU ASAP CAIR TEMPURUNG KELAPA - Ervina Mela Dewi, Yandra Arkeman, Erliza Noor, Noer Azam Achsani (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
Derived products from coconut shell wood vinegar in Indonesia are still limited, consequently need todevelop new products. Critical step of new product development is product concept selection. Currently, productconcept selection has been done based on intuition by decision makers and it mostly gained the fail products.Therefore, it needs to design a decision support system for selecting product concepts of coconut shell woodvinegar with intelligent system. The objective of this study was to obtained the intelligent decision support systemfor selecting new product concept. In detail, the objectives were to gain new product concepts of coconut shellwood vinegar, design success prediction model and design priority and recommendation determination modelfor selecting new product concepts. Literature study was carried out to find the new product concepts,backpropagation artificial neural networks was applied for prediction model, and pairwise comparation alsoBayes method used to design priority and recommendation determination model. The intelligent decision supportsystem for selecting new products concept model can be used to rank priority of coconut shell wood vinegar newproduct concepts. The new products concepts as first priority are supporting products for agriculture includefertilizer, growth hormone, pesticide, herbicide, insecticide, fungicide, and repellent.Keywords: coconut shell wood vinegar, new product concept selection, intelligent decision support system